Participation of Contemporary Pagans in Heritage Politics of Lithuania - Aleknaite, Egle (The pomegranate, 2018)
The paper aims at examining participation of contemporary Lithuanian Pagans (represented by Romuva in this study) in politics of heritagization. After presentation of a broader picture of the research and the revival of ethnic culture during both Soviet and post-Soviet periods, contemporary Pagan discourse and practices intended for society, as well as attempts to make influence through state institutions are analyzed. The case study shows that they interact and compete with other religious groups and inheritors of the past and can employ a range of strategies to seek power and influence in heritage politics. The post-Soviet context that accounts for some specific characteristics of contemporary Eastern European Pagans is also an important factor in heritage politics related to worldview-based competition, and in Lithuanian case, the well-known hostility of contemporary Pagans towards Christianity is accompanied by the threat that representatives of the Catholic Church feel because of the Pagans' influence in heritage politics.